Triple Synchronous Malignancies in Genital Tract; Primary Endometrial, Ovarian and Fallopian Tube Carcinoma: A Case Report - OZGUR KAN; AYSEGUL ALKILIC; BATUHAN TURGAY; ALI GEMICI; CEM SOMER ATABEKOGLU (Journal of Clinical and Diagnostic Research, 2017)
Synchronous malignancies, including three or more tumours, are extremely rare. Herein, we present a case of a woman with a concurrent simultaneous endometrial, ovarian and fallopian tubal carcinoma with different histopathological characteristics. A 55-yearold postmenopausal woman with a diagnosis of endometrial adenocarcinoma by pipelle biopsy, underwent surgical staging. Final pathology result was reported as synchronous stage IA grade 2 endometrioid adenocarcinoma of the uterus, stage IA grade 2 mucinous adenocarcinoma of the right ovary and in situ serous cystadenocarcinoma of the right fallopian tube. In the postoperative period, patient followed without adjuvant therapy. To our knowledge, this a very rare case report in the literature of sychronous triple gynaecologic cancers including fallopian tube cancer and with the longest disease free survival time with over 39 months due to better prognosis than metastatic or advanced primitive diseases.